Comparação da antecipação e do comportamento de busca visual de goleiros experts e novatos em situações de pênalti com e sem informação prévia do batedor - Cristiano Santos da Conceição Ferreira Murta (2020)
This study aimed to compare the anticipation and visual search behavior of soccer goalkeepers in penalty situations with and without previous information from the kicker using the Soccer Goalkeeper Anticipation Assessment Protocol. Forty volunteers, 20 experts (mean age of 18,9 ± 0,8 years and eight-years practice time) and 20 novices (mean age of 19,1 ± 1,1 years and no practice time), participated in the study. The volunteers were submitted to the protocol of evaluation of the goalkeeper anticipation in penalty situation, consisting of 36 penalty scenes, 12 with previous information converging with the result of the kick, 12 with divergent information of the result of the kick and 12 without any previous information. For data analysis, a mixed two-way ANOVA (groups x experimental situations) was used to compare anticipation through total correct answers and visual search through visual fixations (total fixation duration, total fixation duration in each area of interest, total number of fixations) and the precocity and duration of the quiet eye. The significance level was set at 5% and the effect size (Cohen's d) was calculated. In comparisons between groups, the experts obtained more correct answers in situations with wrong information and in situations without information. In addition, the expert group achieved longer fixation in the trunk in situations with the right information and the wrong information than novices. Experts also set more time on the hip in the situations with right and no information. When evaluating the support leg and the kicking leg, the experts presented the highest total mean duration of fixations, in addition to the highest average duration of fixations in the situation without information. In the kicking leg there was a longer average duration of fixations in the situation with wrong information. When all areas of interest were summed up, the experts had the highest total fixation average and had longer fixation in the three experimental situations. Intragroup comparisons showed that the number of correct answers was higher in both groups in the situation with correct information. The experts fixed in the support leg for a longer time in the situation without information compared to the situation with information. Finally, fixation durations in all areas were higher for experts in situations with right information and wrong information than without information. It was concluded that it is important to provide correct prior information to goalkeepers. Experts perform better than novices when the situation presents higher levels of difficulty (divergent and uninformed information). In addition, trunk, hip, support leg, and kicking leg fixations in these situations may provide better quality information for anticipation. More visual fixations on the kicker body can yield better information for anticipation performance.